Religion, Self-Regulation, and Self-Control Associataions, EXplanations, and Implications. [article]. - McCullough, Michael E.
Many of the links of religiousness with health, well-being, and social behavior may be due to religion's influences on self-control or self-regulation. Using Carver and Scheier's (1998) theory of self-regulation as a framework for organizing the empirical research, the authors review evidence relevant.to 6 propositions: (a) that religion can promote self-control; (b) that religion influences how goals are selected, pursued and organized; (c) that religion fascilitates self-monitoring; (d) that religion fosters the development of self-regulatory strength; (e) that religion prescribes and fosters proficiency in a suite of self-regulatory behaviors; and (f) that some religion's influences on health, well-being, and social behavior may results from religion's influences on self-control and self-regulation. The authors conclude with suggestions for future research. -- (from the author)